Pemantauan Proyek Dengan Aplikasi Project Management Menggunakan Laravel - Nyoman Ayu Gita Gayatri; Satrio Ramadhan Soeksmono; Derick Yudanegara; Kevin Lorenzo (Engineering, MAthematics and Computer Science (EMACS) Journal, 2022)
The Internal Division (IT) is a unit that has responsibility for project work and also its completion, the projects handled by the Internal Division (IT) are numerous and also have various specifications. For now, the coordination process is still being carried out using Group Chat on Skype, Whatsapp, and Google Meet so that many obstacles or problems are encountered. Based on the results of interviews with the Head Department in the internal division (IT) there are problems in monitoring the project, project work, project file storage locations, communication media between project teams, project management. The purpose and benefits of the research are to provide convenience for the IT division in conducting the process of managing and monitoring the ongoing project, providing project management services within the organization that can be connected between individuals for project management. Needs analysis was carried out using data collection methods in the form of observations and interviews. The methodology used is Waterfall. The Waterfall development methodology is a development model that flows from the first phase to the last. The problem is that project and progress monitoring is carried out through Skype and Whatsapp social media so that there are many group chats that are less effective in working on a project due to lack of information about the project that is being worked on or the project to be worked on (the status of the project). The final result produces a Project Management Application that is used to manage all projects carried out in the IT Division and is able to handle the problems at hand. The scope of the resulting application monitors the progress of the project; has a forum feature as a medium of communication between project teams; provide a place to store files related to the project being worked on; Equipped with a time schedule feature for project work.